Down-regulation of SFRP1 as a putative tumor suppressor gene can contribute to human hepatocellular carcinoma - Zheng Da-Li; Lin Yun; Teng Xiao-Mei; Zhang Yun-Li; Huang Jian; Yang Peng-Yuan; Han Ze-Guang (BMC Cancer, 2007)
Abstract Background Hepatocellular carcinoma (HCC) is one of the most common cancers in the world. SFRP1 (the secreted frizzled-related protein 1), a putative tumor suppressor gene mapped onto chromosome 8p12-p11.1, the frequent loss of heterozygosity (LOH) region in human HCC, encodes a Wingless-type (Wnt) signaling antagonist and is frequently inactivated by promoter methylation in many human cancers. However, whether the down-regulation of SFRP1 can contribute to hepatocarcinogenesis still remains unclear. Methods We investigated the expression of SFRP1 through real time RT-PCR and immunohistochemistry staining. The cell growth and colony formation were observed as the overexpression and knockdown of SFRP1. The DNA methylation status within SFRP1 promoter was analyzed through methylation-specific PCR or bisulphate-treated DNA sequencing assays. Loss of heterozygosity was here detected with microsatellite markers. Results SFRP1 was significantly down-regulated in 76.1% (35/46) HCC specimens at mRNA level and in 30% (30/100) HCCs indicated by immunohistochemistry staining, as compared to adjacent non-cancerous livers. The overexpression of SFRP1 can significantly inhibit the cell growth and colony formation of YY-8103, SMMC7721, and Hep3B cells. The RNA interference against the constitutional SFRP1 in the offspring SMMC7721 cells, which were stably transfected by ectopic SFRP1, can markedly promote cell growth of these cells. LOH of both microsatellite markers D8S532 and D8SAC016868 flanking the gene locus was found in 13% (6 of 46 HCCs) and 6.5% (3 of 46 HCCs) of the informative cases, respectively, where 5 of 8 HCC specimens with LOH showed the down-regulation of SFRP1. DNA hypermethylation within SFRP1 promoter was identified in two of three HCC specimens without SFRP1 expression. Moreover, the DNA methylation of SFRP1 promoter was significantly reduced, along with the re-expression of the gene, in those HCC cell lines, Bel7404, QGY7701, and MHCC-H, as treated by DAC. Conclusion Our data suggested that the down-regulation of SFRP1 as a candidate tumor suppressor gene, triggered by the epigenetic and/or genetic events, could contribute to the oncogenesis of HCC.